2021
DOI: 10.3389/fonc.2021.723513
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Extradural and Intradural Extension of Pituitary Adenomas to the Suprasellar Region: Classification, Surgical Strategies, and Outcomes

Abstract: ObjectiveSuprasellar pituitary adenomas (PAs) can be located in either extradural or intradural spaces, which impacts surgical strategies and outcomes. This study determined how to distinguish these two different types of PAs and analyzed their corresponding surgical strategies and outcomes.MethodsWe retrospectively analyzed 389 patients who underwent surgery for PAs with suprasellar extension between 2016 to 2020 at our center. PAs were classified into two main grades according to tumor topography and their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Similarly, Yang et al. ( 38 ) described expressly that PAs with intracranial extension had increased surgical complications and a lower rate of gross total removal, although not describing Knosp grades. On the other hand, other authors found that the remission rate was not associated with sellar floor erosion according to the Hardy–Wilson system of grading, neither with supra- and parasellar extension ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Yang et al. ( 38 ) described expressly that PAs with intracranial extension had increased surgical complications and a lower rate of gross total removal, although not describing Knosp grades. On the other hand, other authors found that the remission rate was not associated with sellar floor erosion according to the Hardy–Wilson system of grading, neither with supra- and parasellar extension ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The suprasellar extension will mechanically destroy the structure of the sellar septum. Once the suprasellar extension of pituitary adenomas is located in the dura mater and connected with the skull cavity, it will increase the incidence of surgical complications [12].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the supracarotid height was the distance measured from the midpoint joining both genu of the cavernous internal carotid artery to the most cranial portion of the tumor. 5 On the other hand, the extent of lateral compression, measured by Knosp grading, was recorded, signifying optic nerve compression. 6 Postoperative visual outcomes were assessed with visual acuity (VA), VF, and visual impairment scale (VIS).…”
Section: Methodsmentioning
confidence: 99%